2019
DOI: 10.1038/s41598-018-37837-4
|View full text |Cite
|
Sign up to set email alerts
|

Toxic Injury to Muscle Tissue of Rats Following Acute Oximes Exposure

Abstract: Therapeutic application of newly developed oximes is limited due to their adverse effects on different tissues. Within this article, it has been investigated which morphological changes could be observed in Wistar rats after the treatment with increasing doses of selected acetyl cholinesterase reactivators - asoxime, obidoxime, K027, K048, and K075. Subsequently, heart, diaphragm and musculus popliteus were obtained for pathohistological and semiquantitative analysis 24 hrs and 7 days after im administration o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 72 publications
2
14
0
1
Order By: Relevance
“…As found in the literature, it was confirmed that all reactivators tested at high dosages caused damage to both visceral tissues and the overall health of the individual. The data obtained may be an important support for dose choices regarding different reactivators structures for newly developed drugs [71,72].…”
Section: Ache Reactivation Processesmentioning
confidence: 84%
“…As found in the literature, it was confirmed that all reactivators tested at high dosages caused damage to both visceral tissues and the overall health of the individual. The data obtained may be an important support for dose choices regarding different reactivators structures for newly developed drugs [71,72].…”
Section: Ache Reactivation Processesmentioning
confidence: 84%
“…Our previous study has confirmed that exposure to low, injury-free oxime concentration, which was unable to cause muscle cells’ damage. Further increase in their doses leads to different muscular tissue damages due to their potent cytotoxic and pro-inflammatory effect 25 . Several investigators confirmed this statement in vitro 18,19 , but not so far in vivo 18,19 .…”
Section: Discussionmentioning
confidence: 99%
“…Since all the toxicological data were provided in the earlier studies 25,26 , in this third study, we focused our attention on an investigation of morphological lesions of visceral tissue’s produced by increasing doses of selected AChE reactivators. For this purpose, standard oximes (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Each 2-μm thick paraffin section was stained with hematoxylin and eosin (H&E), and exanimated at a magnification of 200× using a light microscope (BKS-45, Olympus, Japan), according to our previously published methodology [ 9 , 17 , 18 , 19 , 20 , 71 , 72 , 73 , 74 , 75 , 76 , 77 ].…”
Section: Methodsmentioning
confidence: 99%